-6/h=3

Simple and best practice solution for -6/h=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6/h=3 equation:



-6/h=3
We move all terms to the left:
-6/h-(3)=0
Domain of the equation: h!=0
h∈R
We multiply all the terms by the denominator
-3*h-6=0
We add all the numbers together, and all the variables
-3h-6=0
We move all terms containing h to the left, all other terms to the right
-3h=6
h=6/-3
h=-2

See similar equations:

| 10z-22=3(3z+11)-z | | (14x-94)+78=102 | | 3x=2x+4=5x−8 | | -6x-2x=3x | | 25x7=0 | | 38-8m=-6(-7m+2) | | 8x+37+12x+23=360 | | 3k(2k+7)=15 | | 5x+28=-2 | | 8x+37+12x+23=90 | | -7x+16-3x-4=72 | | 4(2+3x)=40 | | 8x+37+12+23=180 | | 17^2x=17^3x-8 | | 16=3x+x | | 6x-14x=16=-35+11 | | 1.29(x+4)=7.20 | | 17^2x=16^3x-8 | | 1/8=1/(2(x+9)^1/2) | | 8x+37=12+23 | | 5x+5x-2=28 | | 17/20=tT9-(13/20) | | 3=3x^2+2+6x | | -4x+3=5x-12 | | (2p-7)(4p+3)=3 | | 2x+6x+3=27 | | 0.05(n-520)=106 | | 2v-7(-3v-7)=-31+7v | | 3x+7=-9-5x | | Y=4+5xX=5 | | -1+m/2=-4 | | 3x-3((12-2x)/3)=3 |

Equations solver categories